(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
The management of information and communication technology in the Enrekang Regency Government is currently still sectoral, so it is necessary to integrate efforts in the development pattern and support for integrated information and communication technology policies. It is necessary to think strategically about programs in planning effective and efficient development for a long period of time, and the optimal impact of internet-based telecommunications information in Enrekang Regency. This research uses qualitative research. With the number of informants as many as 6 people. The results of this study indicate that the target of developing an internet-based telecommunications network is in accordance with what is expected by the government of Erekang Regency. In terms of the policy of developing internet-based telecommunications networks, it is in accordance with the goals expected by the community. There are several programs that are designed and always developed by the government to make it easier for the community. Apart from this, there are several that have been made in the development of internet-based telecommunications networks. Keywords: Government Strategy and Development